2021
DOI: 10.1007/s00431-021-03930-6
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric procedural sedation and analgesia in the emergency department: surveying the current European practice

Abstract: Procedural sedation and analgesia outside the operating theater have become standard care in managing pain and anxiety in children undergoing diagnostic and therapeutic procedures. The objectives of this study are to describe the current pediatric procedural sedation and analgesia practice patterns in European emergency departments, to perform a needs assessment-like analysis, and to identify barriers to implementation. A survey study of European emergency departments treating children was conducted. Through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 65 publications
2
46
0
5
Order By: Relevance
“…Beyond sparse adherence to specific pain treatment with analgesics, the frequency of analgesia for various medical procedures remains uncommon, and incorrect practices continue. Notably, however, there is a slight reduction of hospitals that never use analgesics for these procedures, but analgesia remains rarely used for venipuncture, below the average in Europe and Canada(Ali et al, 2014; Sahyoun et al, 2021), but in line with other international reports(Ali et al, 2014; Kleiber et al, 2011). National and international recommendations, however, clearly suggest the implementation of analgesia when performing venipuncture(Bailey and Trottier, 2016; Bauman and McManus, 2005; Direção-Geral da Saúde, 2012a; Fein et al, 2012; Ruest and Anderson, 2016; Trottier et al, 2019).…”
Section: Discussionsupporting
confidence: 59%
“…Beyond sparse adherence to specific pain treatment with analgesics, the frequency of analgesia for various medical procedures remains uncommon, and incorrect practices continue. Notably, however, there is a slight reduction of hospitals that never use analgesics for these procedures, but analgesia remains rarely used for venipuncture, below the average in Europe and Canada(Ali et al, 2014; Sahyoun et al, 2021), but in line with other international reports(Ali et al, 2014; Kleiber et al, 2011). National and international recommendations, however, clearly suggest the implementation of analgesia when performing venipuncture(Bailey and Trottier, 2016; Bauman and McManus, 2005; Direção-Geral da Saúde, 2012a; Fein et al, 2012; Ruest and Anderson, 2016; Trottier et al, 2019).…”
Section: Discussionsupporting
confidence: 59%
“…This is achieved by the above mentioned safety rules and structured approach (prescreening, structured contact before initiation of pharmacological sedation, structured training) Most patients with ASA 3 or 4 were excluded for sedation by PROSA, because sedation in these categories is prone to more adverse events [ 12 ]. According to a European survey in 2021 of senior physicians, a lack of protocol and training is the main reason for dissatisfaction with management of anxiety and pain in children in their hospital setting [ 13 ]. They also found that only a third of the sites had the complete staff certified in a Pediatric Advanced Life Support course.…”
Section: Discussionmentioning
confidence: 99%
“…Topical and local anaesthesia through the application of anaesthetic creams or injecting buffered lidocaine is the most effective pain relief technique during peripheral intravenous cannulation [ 2 , 15 ]. Nevertheless, a recent survey focused on European paediatric EDs showed that their availability and use is still limited [ 19 ]. Notably in this study, only 3.2% percent of adolescents received EMLA cream compared to 43.8% of older children and 80% of young children.…”
Section: Discussionmentioning
confidence: 99%